Mediating genocide: Cultural understanding through digital and print media stories in global communication. (1st September 2012) - Wessels, Bridgette; Anderson, Bob; Durrant, Abigail; Ellis, Julie
The rise of digital media is creating new ways for media producers and users to engage with stories from around the world. The use of stories is a common way for content to be shared. The global communication space for sharing stories is referred to as the mediapolis, and it incorporates networked interactions mediated through digital technology and traditional media such as print media. The mediapolis generates ways for users to engage with media stories, and its international reach raises concerns about how stories from across the globe can be mutually understood. To address the various ways in which users engage in events of global and ethical significance we discuss the relationship between media (digital and print), media stories and how users are positioned to engage with stories. We explore how the media environment can foster shared understanding amongst users through the use of stories in the mediapolis. To do this we examine memorialisation, focussing on the 1994 Rwandan Genocide. We analyse the print- and web-based stories produced by the Kigali Genocide Memorial (KGM) in Rwanda. We discuss how the medium and the story engender different types of engagement in relation to an event. We develop the concept of the 'hybrid-engager' to show how media users engage with media stories in different ways fostering various levels of understanding. This paper is a positioning exercise for grounding further conceptual development and empirical studies.